Revealing an enabling environment: How clinical community and clinical stakeholders understand peer navigation to improve quality of life for people living with HIV in Australia - Krulic, Timothy; Brown, Graham; Graham, Sara; Hoy, Jennifer; Bourne, Adam (Frontiers in Public Health, 2023)
People living with HIV have unique resources to offer each other and health systems. This study investigated how peer navigation contribute to a socially supportive, health enabling environment in Victoria, Australia. We used semi-structured interviews with 30 program staff, management, peer workers and clinician stakeholders. Our analyses considered the interplay between the program, users, HIV-related stigma and discrimination and the health service environment. Peer relationships offered reassurance, acceptance and belonging, which people living with HIV can use to create personal change. Peer engagement coproduced insights for life with HIV and may help to overcame stigma and structural barriers to access services and community support. As a partnership between peer and clinical services, participants described how the program fostered appreciation of peer practices and insights, which were used to improve the quality and continuity of care offered in the state. These findings allude to the value of the community engagement and policy alignment peer responses produce and can be used to guide implementation of similar programs elsewhere.